Assessment of Parental Social Stigma Across Three Testing Phases: A Comparative Analysis Between Study and Control Groups - Tameem Yeakoob Ibrahem; Arfat H. Al-Dujaili (مجلة الكوفة الطبية, 2025)
Background: This study aims to evaluate the effect of a psycho-educational program on reducing social stigma among parents of children with epilepsy. The research was conducted on two groups (intervention and control), each consisting of 50 participants from the Psychiatric Diseases Center at Al-Hakim General Hospital in Najaf, Iraq. Three assessment tools were used to measure the level of social stigma before and after the intervention. The results showed a significant decrease in social stigma levels among the intervention group who received the psychological program, compared to the control group who received no intervention. It is concluded that psycho-educational programs effectively contribute to improving the psychological and social well-being of parents of children with epilepsy.